2020
DOI: 10.1177/0972150920934640
|View full text |Cite
|
Sign up to set email alerts
|

Transformational Leadership’s Impact on Organizational Innovation: The Mediating Role of Management Control System

Abstract: Contemporary organizations are made up of various tangible and intangible components. While several of these components have been subjected to a variety of scholarly studies, both individually and in relation to one another, a number of organizational components still require deeper investigation. The present study looks at the direct and indirect effects of transformational leadership (TL) on organizational innovation (OI) through management control system (MCS) as a mediating variable. This objective has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 98 publications
0
1
0
Order By: Relevance
“…Participatory leaders who make decisions about projects by taking into account of their team members' decisions are able to encourage employees' creativity (Creţu, 2015). Alharbi et al (2020) showed that in the context of Saudi Arabia, transformational leadership contributed to subordinates' self-esteem, confidence and efficacy, motivating them to adopt innovative ways in performing their tasks beyond expected performance. Meanwhile, other empirical studies have evidenced the use of MCS (e.g., the use of specific performance measures, the delegation of decision rights or the use of planning systems) is dependent to some extent on individual differences, such as leadership styles (e.g., Jansen, 2011).…”
Section: Formal Mcs Innovation and Leadership Characteristicsmentioning
confidence: 99%
“…Participatory leaders who make decisions about projects by taking into account of their team members' decisions are able to encourage employees' creativity (Creţu, 2015). Alharbi et al (2020) showed that in the context of Saudi Arabia, transformational leadership contributed to subordinates' self-esteem, confidence and efficacy, motivating them to adopt innovative ways in performing their tasks beyond expected performance. Meanwhile, other empirical studies have evidenced the use of MCS (e.g., the use of specific performance measures, the delegation of decision rights or the use of planning systems) is dependent to some extent on individual differences, such as leadership styles (e.g., Jansen, 2011).…”
Section: Formal Mcs Innovation and Leadership Characteristicsmentioning
confidence: 99%